Endogenous acrolein accumulation in akr7a3 mutants causes microvascular dysfunction due to increased arachidonic acid metabolism - Zhang, Xin; Gschwind, Johannes; Erben, Vanessa; Bennewitz, Katrin; Li, Xiaogang; Sticht, Carsten; Poschet, Gernot; Haußer-Siller, Ingrid; Fleming, Thomas; Szendrödi, Julia; Nawroth, Peter Paul; Kroll, Jens (Redox Biology, 2025)
Acrolein (ACR) is an endogenous reactive unsaturated aldehyde that can be detoxified by the aldo-keto reductase (AKR) enzyme system. While it has been shown that accumulation of ACR is associated with several health problems, including inflammation, oxidative stress, and cardiovascular disease the study aimed to analyze whether an endogenous accumulation of ACR is causal for vascular dysfunction in an akr7a3 mutant zebrafish model. Enlargement of the hyaloid and retinal vasculature, as well as alterations in the larval pronephros and thickening of the glomerular basement membrane in the adult kidney were found upon ACR accumulation. Transcriptomic and metabolomic analyses, followed by functional validation, revealed that the up-regulation of genes controlling the arachidonic acid metabolism and activation of the leukotriene pathway are responsible for the observed microvascular changes. In conclusion, the data have identified an intrinsic function of ACR in akr7a3 mutants that activates the arachidonic acid metabolism and subsequently disrupts vascular integrity by promoting an inflammatory response. Thus, ACR is causal in the development of vascular disease.